KONFIRMASI TEKNIK PENGAMBILAN SAMPEL UNTUK SELEKSI LAJU DAN MASA PENGISIAN BIJI TANAMAN JAGUNG - Teuku Mahmud (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2009)
Confirmation of Sampling Technique for Selection of Rate and Filling Periode Duration in Corn Teuku Mahmud Fakultas Pertanian Unsyiah, Darussalam Banda Aceh ABSTRACT Kernels of the original (C0) plus fifth cycle (C5) of a maize (Zea mays L.) synthetic, divergently selected for long and short effective filling period (EFP) or high and low dry matter accumulation rate (DMAR), were evaluated by two different sampling procedures. The objectives were to evaluate single plant vs. multiple plant measurement procedure for EFP and DMAR, plus changes the selection traits, physiological and morphological characteristics, and plant yield. The two sampling techniques and all data analysis procedures resulted in a similar ranks of kernel size, DMAR, and EFP. The best estimate of maximum kernel size was at black layer maturity. The nonlinear procedure estimated EFP better than did other procedures. Compared to C0, DMAR was increased 31.5% and reduced 36% for the C5 high and low DMAR subpopulations, respectively. The kernel size of high and low DMAR in C5 differed by 105.4%. Long EFP selections tended to decreased DMAR. Compared to C0, EFP was increased 11.3% and reduced 8.8% for the C5 long and short EFP subpopulations, respectively. The EFP differences between long and short EFP selections was 22.1%. Duration differences occured almost exclusively in the late lag phase. Yield of the long EFP and high DMAR selections were equal to C0 but significantly greatert than short EFP and low DMAR selections. Yield was positively correlated with kernel size, DMAR, and EFP. Kernel size was correlated with DMAR and yield. From this experiment one might infer that selection for long EFP and high DMAR should increase yield.